2014
DOI: 10.1186/s40490-014-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing natural regeneration of totara (Podocarpus totara D.Don) on grazed hill country grassland in Northland, New Zealand

Abstract: Background: There is increasing interest in establishing indigenous forests on marginal pastoral hill country in New Zealand to improve soil conservation, water quality and indigenous biodiversity. Large-scale reforestation using native seedlings is extremely costly. However, given suitable seed sources, it is possible to encourage natural regeneration of grassland into native plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…This study revealed a low rate of natural regeneration of woody vegetation from pasture on Oashore Station of approximately 0.2% per year. This quantifies the more general findings regarding slow colonization of grassland by forest plants in similar locations (Reay & Norton 1999) and provides an overall rate of regeneration across an entire site that is lacking in other studies in temperate regions utilizing representative field plots (Mason et al 2013;Bergin & Kimberley 2014;Forbes et al 2021). The rate of regeneration is broadly comparable to international studies using remote sensing methods, with tree cover in tropical regions of Brazil (which typically experience faster growth) found to increase by 0.3% per year (Crouzeilles et al 2020;Borda-Niño et al 2021) and 0.4% per year (de Rezende et al 2015).…”
Section: Observed Rate Of Natural Regeneration Of Woody Vegetationmentioning
confidence: 63%
“…This study revealed a low rate of natural regeneration of woody vegetation from pasture on Oashore Station of approximately 0.2% per year. This quantifies the more general findings regarding slow colonization of grassland by forest plants in similar locations (Reay & Norton 1999) and provides an overall rate of regeneration across an entire site that is lacking in other studies in temperate regions utilizing representative field plots (Mason et al 2013;Bergin & Kimberley 2014;Forbes et al 2021). The rate of regeneration is broadly comparable to international studies using remote sensing methods, with tree cover in tropical regions of Brazil (which typically experience faster growth) found to increase by 0.3% per year (Crouzeilles et al 2020;Borda-Niño et al 2021) and 0.4% per year (de Rezende et al 2015).…”
Section: Observed Rate Of Natural Regeneration Of Woody Vegetationmentioning
confidence: 63%
“…and Tōtara ( Podocarpus totara ; Smale et al . ; Bergin & Kimberley ), although successions through exotic species towards native dominance are also widespread (Wilson ; Sullivan et al . ).…”
Section: Recommendationsmentioning
confidence: 99%
“…Many successions are through native seral species such as K anuka (Kunzea spp.) and T otara (Podocarpus totara; Smale et al 1997;Bergin & Kimberley 2014), although successions through exotic species towards native dominance are also widespread (Wilson 1994;Sullivan et al 2007). While much of the focus in conservation is on protecting remnants of original ecosystems, regenerating vegetation also has important values and its protection should be a priority, both legal protection and protection of the successional processes.…”
Section: Active Regrowth Of Native Woody Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, P. totara is light demanding and has a rapid growth response to canopy opening (Ebbett & Ogden ). Podocarpus totara is known to regenerate most vigorously in high‐light environments such as large windthrow gaps and forest margins, among open scrub (McSweeney ), and even in grazed exotic grassland (Bergin & Kimberley ).…”
Section: Introductionmentioning
confidence: 99%